If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -6 = -2x + -30 Reorder the terms: -6 + 2x = -2x + -30 Reorder the terms: -6 + 2x = -30 + -2x Solving -6 + 2x = -30 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -6 + 2x + 2x = -30 + -2x + 2x Combine like terms: 2x + 2x = 4x -6 + 4x = -30 + -2x + 2x Combine like terms: -2x + 2x = 0 -6 + 4x = -30 + 0 -6 + 4x = -30 Add '6' to each side of the equation. -6 + 6 + 4x = -30 + 6 Combine like terms: -6 + 6 = 0 0 + 4x = -30 + 6 4x = -30 + 6 Combine like terms: -30 + 6 = -24 4x = -24 Divide each side by '4'. x = -6 Simplifying x = -6
| 8+6+w=208 | | -4(6-x)+3=2(x-3) | | -0.2+13=-6 | | 25x-24=3(6x-6)+7x-6 | | -4b+5=-15+b+5-7b | | 15x-3(-8)=-6 | | .6(x-2)=14.4 | | -2x+210=7x-15 | | -2x+8=2(x+4) | | Y+5x=78 | | 300=9+12x | | -3(-1x+6)=-15 | | 300=12x+9 | | 5x+7+30=-8+3x | | y=2abs(x+1) | | 2.68d+2.04=1.02+6.1 | | (4y+26)(3x-5)= | | 7-15=3x+1 | | 9x+25=2x+6 | | 3+2(3n+2)=-41 | | .5x+3=.75x-7.75 | | 12(x)+9=300 | | 41k+11=16 | | 5=7+2x | | 12x+(7-x)2= | | x/3=2/9 | | 2(x+10)=4(x-2) | | -8(4+9x)=3(x-1) | | 25t+30b=750 | | 3x+1=1-3x | | -60+40x=20x | | (t)+2.7=4.5 |